2016
DOI: 10.1038/pr.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors and practice trends in red blood cell transfusions for very-low-birth-weight infants

Abstract: Background Red blood cell (RBC) transfusions in very low birthweight (VLBW) infants, while common, carry risk. Our objective was to determine clinical predictors of and trends in RBC transfusions among VLBW infants. Methods RBC transfusion practice and its clinical predictors in 1,750 VLBW (≤1500 g) infants were analyzed in a single-center cohort across sequential epochs: 2000–2004 (Epoch 1), 2005– 2009 (Epoch 2), and 2010–2013 (Epoch 3). Results Overall, 1,168 (67 %) infants received ≥1 transfusions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Therefore, the concentrations of systemic VEGF and other angiogenic cytokines have been evaluated in a variety of different set-ups with the intention to identify either systemic predictors of pathogenic retinal angiogenesis or changes in expression of such factors as a consequence of systemic VEGF-blockage by intravitreal anti-VEGF therapy 914 . However, repeated phlebotomy loss in the first weeks of life is one of the major causes of iatrogenic anaemia, and can significantly contribute to the exposure to red blood cells transfusions 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the concentrations of systemic VEGF and other angiogenic cytokines have been evaluated in a variety of different set-ups with the intention to identify either systemic predictors of pathogenic retinal angiogenesis or changes in expression of such factors as a consequence of systemic VEGF-blockage by intravitreal anti-VEGF therapy 914 . However, repeated phlebotomy loss in the first weeks of life is one of the major causes of iatrogenic anaemia, and can significantly contribute to the exposure to red blood cells transfusions 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Temporal trends suggest increasingly restrictive RBC transfusion practices, with acceptance of a lower concentration of Hb before a RBC transfusion [14][15][16] . In the absence of a clear advantage of either approach, the optimal Hb transfusion threshold remains uncertain with a recent Cochrane review justifying clinical equipoise 17 .…”
Section: Overview Of Transfusion Practicesmentioning
confidence: 99%
“…Taken together, a metaanalysis in 2011 including a long-term study by Whyte et al [ 33 ] showed the following findings: (1) the restrictive group received fewer transfusions and lowered donor exposures than the liberal group, (2) there were no differences between both groups in the rate of mortality and serious morbidity at discharge, and (3) there were no differences between both groups at 18 to 21 months of corrected age in mortality, major morbidity, and serious neurodevelopmental impairment [ 34 ]. Based on these findings, use of the restrictive strategy is preferred to decrease exposure to transfusions [ 35 ]. Transfusion should be carefully determined by comparing the anticipated effects and risks according to the clinical condition as well as the hematocrit level.…”
Section: Current Trends and Practices Of Rbc Transfusion In Neonatesmentioning
confidence: 99%